Distinct responses of diatom- and flagellate-dominated Antarctic phytoplankton communities to altered iron and light supply - Camoying, Marianne; Koch, Florian; Stimpfle, Jasmin; Pausch, Franziska; Hassler, Christel; Trimborn, Scarlett (Frontiers in Marine Science, 2024)
Primary production in the Southern Ocean is strongly influenced by the availability of light and iron (Fe). To examine the response of two distinct natural Antarctic phytoplankton communities (diatom vs. flagellates) to increasing light and Fe availability, we conducted two shipboard incubation experiments during late summer and exposed each community to increasing light intensities (30, 80, and 150 µmol photons m−2 s−1) with or without Fe amendment. Our results show clearly that both communities were Fe-limited since Fe addition resulted in higher particulate organic carbon (POC) production rates. The magnitude of the Fe-dependent increase in POC production, however, varied between the two stations being higher in the diatom-dominated community relative to the flagellate-dominated community. This differential response to increasing Fe supply could be attributed to the higher Fe requirement of the flagellate-dominated assemblage relative to the diatom-dominated assemblage. Irrespective of Fe availability, light also strongly stimulated the POC production of both communities between low and medium light supply (30 versus 80 µmol photons m−2 s−1), indicating that both assemblages were light-limited in situ. However, since POC production of both communities did not increase further at the highest light intensity (150 µmol photons m−2 s−1) even under high Fe supply, this suggests that light supply was saturated or that other conditions must be fulfilled (e.g., availability of trace metals other than Fe) in order for the communities to benefit from the higher light and Fe conditions.